A study of the effects of row spacing and sowing rate on growth, seed yield and seed quality of safflower (Carthamus tinctorious L.) : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agriculture Science at Massey University - Raffar, Khalip Abdul (Massey University, 1974)
Major Interest in the potential of oil seed crop in New Zealand agriculture has been shown over the past few years. Through extensive research, soybean has been successfully established as a crop in local agriculture. This is evident by the substantial increase in soybean acreage (2000 - 3000) in the Gisborne area this year. In the South Island, oil seed crop such as sunflower has also been grown successfully. The main interest in oilseed crop production is the oil and its composition. Vegetable oils which contain high level of polyunsaturated fatty acids are highly sought after because of their low cholesterol property. In the past, this type of oil has been used mainly for making low cholesterol content margarine and cooking. However, the recent interest in easy-spread butter and the discovery by research scientists of the C.S.I.R.O. in Australia that feeding stock with vegetable oils containing poly-unsaturated fatty acids reduces cholesterol levels in both meat and milk have increased interest in oilseed crop in this country. [From Introduction]
Keywords: Safflower; Seeds; Safflower Spacing